Association of race and gender with primary caregiver relationships and eligibility for advanced heart failure therapies. Issue 1 (26th October 2021) - Steinberg, Rebecca S.; Nayak, Aditi; Burke, Michael A.; Aldridge, Morgan; Raja Laskar, S.; Bhatt, Kunal; Sridharan, Lakshmi; Abdou, Mahmoud; Attia, Tamer; Smith, Andrew; Daneshmand, Mani; David Vega, J.; et al.
Abstract: Background: Caregiver support is considered necessary after heart transplant (HT) and left ventricular assist device (LVAD) for patients with end‐stage heart failure (HF). Few studies have demonstrated how caregivers differ by gender and race, and whether that impacts therapy eligibility. Methods: We examined caregiver relationships among 674 patients (32% women, 55% Black) evaluated at Emory University from 2011 to 2017. Therapy readiness was assessed using the Stanford Integrated Assessment for Transplant (SIPAT). Evaluation outcome according to caregiver relationship was compared using χ 2 analysis. Multivariable logistic regression determined the association between caregiver and eligibility according to gender and race. Results: Women and Black patients were less likely to have spouses as their support person ( P < .001). Women were less likely to be considered eligible for advanced therapies (adjusted odds ratio [aOR] .64, 95% confidence interval [CI] .46–.89; P = .008), with Black women having lower eligibility than White women (aOR .28, 95% CI .11–.72; P = .008). Social support and SIPAT scores did not significantly influence eligibility by gender or race. Conclusion: Lack of caregiver support is considered a relative contraindication to advanced therapies. Type of caregiver in our cohort varied according to race and gender but did not explain differences in eligibility for advanced therapies.